PROFIL USAHA SERAT PISANG ABAKA DI KELURAHAN MAKTARA KABUPATEN KEPULAUAN TALAUD (Profile of Abaka Banana Fiber in Maktara Village, Talaud Islands Regency) - Novisye Grace Sandari; Vicky R. B. Moniaga; Olfie L. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to describe the business profile of abaka banana fiber in Makatara Village, Talaud Islands Regency, which lasted for three months, starting from October to December 2019, in Makatara Village, Talaud Islands Regency. The data used in this study are primary data and secondary data. then analyzed descriptively.The results showed that the business profile of abaka banana fiber in Makatara Village, Talaud Islands Regency was (1) A hand craft business that had produced various types of hats, bags, lanterns, pineapple lanterns, serving covers, bete flowers, in which there is a group called the Rintulu Maelonan group as a group that manages the abaka banana fiber business as a handicraft material. (2) The raw materials used are obtained from the garden of Mr. Adrianus.Ontoge as the head of the Rintulu Maelonan group. For the production process using simple tools and materials, the packaging process is still manual by hand, with simple equipment capable of creating products from abaca banana fiber. The form of marketing used in the Rintulu Maelonan group makes two forms of marketing, namely direct marketing and online marketing.